Dopamine neurons implanted into people with Parkinson's disease survive without pathology for 14 years - Mendez, Ivar; Viñuela, Angel; Astradsson, Arnar; Mukhida, Karim; Hallett, Penelope; Robertson, Harold; Tierney, Travis; Holness, Renn; Dagher, Alain; Trojanowski, John Q; Isacson, Ole (Nature medicine, 2008)
Postmortem analysis of five subjects with Parkinson's disease 9–14 years after transplantation of fetal midbrain cell suspensions revealed surviving grafts that included dopamine and serotonin neurons without pathology. These findings are important for the understanding of the etiopathogenesis of midbrain dopamine neuron degeneration and future use of cell replacement therapies.